2010
DOI: 10.1039/c002241a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for role of transmembrane helix–helix interactions in the assembly of the Class II major histocompatibility complex

Abstract: The Major Histocompatibility Complex Class II (Class II MHC) and invariant chain (Ii) proteins are key initiators of an immune response to invading pathogens. Following biosynthesis, three MHCalpha/beta hetero-dimers associate with an Ii homotrimer to form a nine-chain protein complex. Only as part of this complex are the MHC molecules exported to the cell surface to trigger an immune response. Previous reports implicate the transmembrane (TM) domains of all three proteins in correct assembly, ligand binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 67 publications
6
53
0
Order By: Relevance
“…Lipid raft-resident Ia.2 ϩ class II molecules drive Src family kinase-dependent calcium signaling in mature B cells and, consistent with the work of Roche and co-workers (17)(18)(19), are critically important for B cell antigen presentation and formation of B cell-T cell conjugates (5). Previous studies also suggested a role for TM domain GXXXG dimerization motifs in MHC class II ␣-␤ chain pairing (15). In this study, we provide a molecular explanation for the role of these motifs in determining MHC class II conformer formation by showing that differential pairing of the class II ␤ chain GXXXG motif with one of two ␣ chain motifs drives or enables formation of Ia.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Lipid raft-resident Ia.2 ϩ class II molecules drive Src family kinase-dependent calcium signaling in mature B cells and, consistent with the work of Roche and co-workers (17)(18)(19), are critically important for B cell antigen presentation and formation of B cell-T cell conjugates (5). Previous studies also suggested a role for TM domain GXXXG dimerization motifs in MHC class II ␣-␤ chain pairing (15). In this study, we provide a molecular explanation for the role of these motifs in determining MHC class II conformer formation by showing that differential pairing of the class II ␤ chain GXXXG motif with one of two ␣ chain motifs drives or enables formation of Ia.…”
Section: Discussionsupporting
confidence: 58%
“…However, there is at least one potential explanation for this finding. Previous studies established that ␤ chain pairing to the ␣ chain M1 motif is significantly less robust than pairing to the M2 motif (15). Therefore, it is possible that the presence of two large side chain residues (e.g.…”
Section: A Role For Transmembrane Gxxxg Dimerization Motifs In Formatmentioning
confidence: 96%
See 2 more Smart Citations
“…The hetero-interactions of the TMDs within a natural membrane environment were studied using the GALLEX assay (24,25 Fig. 1 (without the two Lys at both termini), and those of glycophorin A (GpA) and its G83I mutant, used as positive and negative controls, respectively, are ITLIIFGVMAGVIGTILLI and ITLIIFGVMAIVIGTILLI.…”
Section: Construction Of the Gallex Chimeramentioning
confidence: 99%